O uso da Libras sob a perspectiva das figuras de linguagem - Graciele Kerlen Pereira Maia (2023)
Since the recognition of the linguistic status of sign languages, several studies have reaffirmed that spatial-visual languages are a form of language endowed with a grammatical structure, thus being natural languages, as well as oral-auditory languages. Given this, and the need to expand and enrich systematic knowledge about sign languages, figures of speech constitute a fruitful and highly relevant field of study for the expansion and consolidation of the specificities of sign languages. Therefore, the objective of this work is to identify figures of speech in Brazilian Sign Language (Libras) and their use, based on the parallel between the concept of figures of speech in spoken languages and its equivalent in Libras; look for similarities between the occurrence of these resources in Libras and in oral languages; understand the importance of using such a resource so that Libras speakers can express their discursive particularities. The relevance of this study lies in contributing significantly to Libras studies, honoring and respecting its specificities. The methodology used is a qualitative approach with an exploratory objective and documentary procedure. As a methodological resource, ELAN and Microsoft Paint software were used. This study takes place in three stages: a conceptual theoretical study; collection of productions in Libras to compile the corpus; video analysis. Since the recognition of the linguistic status of sign languages, several studies have reaffirmed that spatial-visual languages are a form of language endowed with a grammatical structure, thus being natural languages, as well as oral-auditory languages. Given this, and the need to expand and enrich systematic knowledge about sign languages, figures of speech constitute a fruitful and highly relevant field of study for the expansion and consolidation of the specificities of sign languages. Therefore, the objective of this work is to identify figures of speech in Brazilian Sign Language (Libras) and their use, based on the parallel between the concept of figures of speech in spoken languages and its equivalent in Libras; look for similarities between the occurrence of these resources in Libras and in oral languages; understand the importance of using such a resource so that Libras speakers can express their discursive particularities. The relevance of this study lies in contributing significantly to Libras studies, honoring and respecting its specificities. The methodology used is a qualitative approach with an exploratory objective and documentary procedure. As a methodological resource, ELAN and Microsoft Paint software were used. This study takes place in three stages: a conceptual theoretical study; collection of productions in Libras to compile the corpus; video analysis. The research is based on the perspective of stylistics, considering that stylistics is concerned with the style of language, enabling the expression not only of the understanding of the world, but, in it, language can be used for aesthetic and expressive purposes, giving the word data emotional. Figures of speech are far from being considered just decorative, they are important as an integral function of language as a whole; This occurs because the relevant cognitive structures surrounding figures are important, pervasive and depart from thought through the enunciator's choices and, as a result, the figurative and/or literal meaning is part of the basis of the linguistic structure. In other words, the act of saying (or writing, drawing, signing, or expressing) something to create unusual meanings reveals pervasive patterns between language, thought, and cognition. The figures analyzed were: Euphemism, Hyperbole, Prosopopeia, Antithesis, Comparison, Gradation and Onomatopoeia. Although the attention of several scholars of sign languages, especially Libras, has already turned to Figures of Speech, much of the research already undertaken and in progress is dedicated to understanding just some of the various known figures of speech, in highlighting metaphor and metonymy, and studying translations from Portuguese to Libras. There are no studies that are dedicated exclusively to verifying the figures of speech in and from Libras, so this is an unprecedented thesis. Therefore, the results of this work are reflections and content that can contribute significantly to the Libras area, honoring and respecting its specificities. The figures analyzed were: Euphemism, Hyperbole, Prosopopeia, Antithesis, Comparison, Gradation, Anaphora and Onomatopoeia. Although the attention of several scholars of sign languages, especially Libras, has already turned to Figures of Speech, much of the research already undertaken and in progress is dedicated to understanding just some of the various known figures of speech, in highlighting metaphor and metonymy, and studying translations from Portuguese to Libras. There are no studies that are dedicated exclusively to verifying the figures of speech in and from Libras, so this is an unprecedented thesis. Therefore, the results of this work are reflections and content that can contribute significantly to the Libras area, honoring and respecting its specificities.